Análise termoelástica experimental e computacional por elementos finitos da parede externa em concreto armado de um forno de cozimento de anodo - TEIXEIRA, Marcelo Rassy (Universidade Federal do Pará, 2011)
This thesis presents a study about the behavior of a reinforced concrete structure subjected to high thermal variations. The structure under investigation is the external wall of an anode furnace used in Aluminum production, and is subjected to thermal variations in the range of 125C (2282 F) due to the furnace operation. The main motivations for the study were the presence of large deformations and occurrence of cracks in the structure, which could cause the furnace to become inoperable. The objective of the research was to investigate the causes of these structural pathologies, as well as to establish retrofit proposals for the structure. For this purpose, experimental and numerical studies were carried out. At first, the structure was monitored using displacement transducers and temperature sensors (thermocouples) connected to a data acquisition system, which could automatically obtain and store samples along the test period. Next, computer models were developed, using a multiphysics Finite Element Code called Algor, for the evaluation of temperature distribution and corresponding thermal stresses and strains in the structure. In these studies, stationary and transient heat conduction analyses were performed, followed by thermal stress analyses. As a conclusion of this research, it can be stated that the proposed methodology, based on advanced tools of structural engineering, was very suitable for the study of the presented phenomenon, since it rendered a precise and economic solution for the problem.